2014
DOI: 10.4149/endo_2014_02_87
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin as a novel therapeutic option for type I diabetes and diabetic osteopathy

Abstract: The results suggest that activation of the oxytocin receptor (OTR) pathway by infusion of OT, OT analogs, or OT agonists may represent a promising approach for the treatment of diabetes and some of its complications, including diabetic osteopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…Previous translational studies stemming from in vitro models to in vivo diabetic models have made headway in developing these therapeutic approaches that specifically target osteoblasts and/or osteoclasts. Among those are the treatments with insulin, PTH, oxytocin, zinc supplement, and sclerostin antibody that have stimulatory effects on osteoblastogenesis and modulatory effects on osteoclast function and formation, which improve bone loss and/or healing . With the emergence of the osteocyte as a key player in diabetic skeletal complications, we expect that future preclinical and translational studies will focus on development and testing of novel osteocyte‐targeted therapeutic interventions, either as an alternative or in combination with osteoanabolic approaches to improve treatment of skeletal dysfunction in diabetic patients.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Previous translational studies stemming from in vitro models to in vivo diabetic models have made headway in developing these therapeutic approaches that specifically target osteoblasts and/or osteoclasts. Among those are the treatments with insulin, PTH, oxytocin, zinc supplement, and sclerostin antibody that have stimulatory effects on osteoblastogenesis and modulatory effects on osteoclast function and formation, which improve bone loss and/or healing . With the emergence of the osteocyte as a key player in diabetic skeletal complications, we expect that future preclinical and translational studies will focus on development and testing of novel osteocyte‐targeted therapeutic interventions, either as an alternative or in combination with osteoanabolic approaches to improve treatment of skeletal dysfunction in diabetic patients.…”
Section: Clinical Relevancementioning
confidence: 99%
“…21,22 In recent research, oxytocin has shown positive metabolic effects on insulin sensitivity, glucose metabolism, and lipid profile in diabetic rats. 23 Moreover, it has an anabolic effect on bone biology. 24,25 As we know, UC is implied as a systemic disease associated with diabetes mellitus, hypertension, gout, and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, OT can improve autism, depression, and other mental disorders associated with immune disorders (71) and increase resistance of enterocyte apoptosis (48) while reducing the apoptosis of rat mesenchymal stem cells (20), and promoting regenerative capacity of skeletal muscle (46) and pancreatic islet cells of diabetic rats (47). …”
Section: Immune Functions Of the Ossmentioning
confidence: 99%